2009
DOI: 10.1074/jbc.m806561200
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin, a Regulator of the 25-Hydroxyvitamin D3 1α-Hydroxylase Gene

Abstract: Although parathyroid hormone (PTH) induces 25-hydroxyvitamin D 3 (25(OH)D 3 ) 1␣-hydroxylase (1␣(OH)ase) underhypocalcemic conditions, previous studies showed that calcitonin, not PTH, has an important role in the maintenance of serum 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) under normocalcemic conditions. In this study we report that 1␣(OH)ase transcription is strongly induced by calcitonin in kidney cells and indicate mechanisms that underlie this regulation. The transcription factor C/EBP␤ is up-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 58 publications
(76 reference statements)
5
52
0
3
Order By: Relevance
“…Since calcitonin levels as well as 1,25(OH) 2 D 3 levels are elevated during lactation, early studies suggested that calcitonin may have a role to stimulate CYP27B1 resulting in increased plasma 1,25(OH) 2 D 3 and increased intestinal calcium absorption during lactation when the need for calcium is increased (427). Studies have shown an effect of calcitonin on CYP27B1 transcription (521). In addition to calcitonin, prolactin, which is also elevated during lactation, has been reported to stimulate renal CYP27B1 (382).…”
Section: E Regulation Of Renal Cyp27b1 and Cyp24a1mentioning
confidence: 99%
“…Since calcitonin levels as well as 1,25(OH) 2 D 3 levels are elevated during lactation, early studies suggested that calcitonin may have a role to stimulate CYP27B1 resulting in increased plasma 1,25(OH) 2 D 3 and increased intestinal calcium absorption during lactation when the need for calcium is increased (427). Studies have shown an effect of calcitonin on CYP27B1 transcription (521). In addition to calcitonin, prolactin, which is also elevated during lactation, has been reported to stimulate renal CYP27B1 (382).…”
Section: E Regulation Of Renal Cyp27b1 and Cyp24a1mentioning
confidence: 99%
“…147, 226 The feedback inhibition of 1a-hydroxylase by 1,25(OH) 2 D 3 is mostly due to inhibition of PTH and the cAMP pathways. 21 Plasma phosphate concentration is also involved in the control of 1,25(OH) 2 D 3 production.…”
Section: Biology Of Vitamin D Activation Of Vitamin Dmentioning
confidence: 99%
“…1,25(OH) 2 D 3 production in the kidney is regulated positively by many factors, including parathyroid hormone (3) and regulated negatively by others (4), including the phosphate hormone FGF23 (5,6). CYP27B1 is also down-regulated by 1,25(OH) 2 D 3 itself, which exerts strong negative feedback control on CYP27B1 transcription to curb 1,25(OH) 2 D 3 synthesis (3,(7)(8)(9).…”
mentioning
confidence: 99%